The Impact of Dialogical Approaches in Extension Programs on Changing Mothers' Behavior for Stunting Prevention in Rural Areas - Hadiyanti , Puji; Irvansyah, Adi; Sasmita, Karta; Br Dalimunthe, Henny Herawaty; Affandi, Muhammad (Universitas Negeri Semarang, 2024)
In Indonesia, numerous initiatives have been implemented to address the issue of stunting; however, these efforts have yet to yield optimal results. This study aims to critically evaluate the effectiveness of an extension program that utilizes a dialogical approach in modifying maternal behaviors related to the provision of adequate nutrition for their children. In the context of non-formal education, extension serves as a crucial learning process for adults, particularly in enhancing their overall quality of life. The research was conducted using a quantitative methodology, employing survey techniques to gather data, which were subsequently analyzed using both descriptive and inferential statistical methods. This study is among the first to empirically compare dialogical and traditional extension approaches within the context of rural Indonesia, providing robust quantitative evidence that interactive, collaborative learning environments significantly outperform conventional one-way communica-tion models in promoting sustainable behavioral changes among mothers. The findings reveal that the extension program, when executed with a dialogical approach, exerts a significant positive influence on altering mothers' nutritional practices for their children. This outcome stands in stark contrast to traditional, linear extension models, which typically rely on one-way communication from the instructor to the participants. In contrast, the dialogical approach fosters an interactive environment where mothers are encouraged not only to ask questions and share personal experiences but also to engage in a more collaborative learning process that ultimately enhances their behavioral change towards better nutrition.